Flexural and tensile strengths of unidirectional hybrid epoxy composites reinforced by S-2 glass and T700S carbon fibres - Dong, Jonathan; Davies, Ian (Elsevier, 2014)
A study on the flexural strength of hybrid epoxy composites reinforced by S-2 glass and T700S carbon fibres in an intra-ply configuration is presented in this paper. The flexural strength was obtained from the three point bend test in accordance with ASTM: D790-10 at various span-to-depth ratios. Nonlinear large displacement finite element analysis (FEA) and the classic lamination theory (CLT) were employed to model the flexural behaviour of the hybrid composites. The models were validated using the experiment specimens from a previous study. With the aid of the developed models, the effects of fibre volume fractions, hybrid ratio and span-to-depth ratio were studied. It is shown that the flexural strength increases with span-to-depth ratio and converges when the span-to-depth ratio is greater than 32. Hybridisation can be used to improve the flexural strength. The hybridisation phenomena are dependent on the strength ratios of carbon/epoxy and glass/epoxy laminas. The overall maximum flexural hybrid effect is achieved when the hybrid ratio is 0.25 ([02G/06C]) when both Vfc and Vfg are 70%. The strength increases are 16.6% and 42.58% when compared with those of the full carbon and glass configurations, respectively. The overall maximum tensile hybrid effect is achieved when the hybrid ratio is 0.125 ([0G/07C]) when Vfc is 30% and Vfg is 50%.